2011
DOI: 10.1111/j.1469-8137.2011.03711.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana nucleosidase mutants provide new insights into nucleoside degradation

Abstract: A central step in nucleoside and nucleobase salvage pathways is the hydrolysis of nucleosides to their respective nucleobases. In plants this is solely accomplished by nucleosidases (EC 3.2.2.x).To elucidate the importance of nucleosidases for nucleoside degradation, general metabolism, and plant growth, thorough phenotypic and biochemical analyses were performed using Arabidopsis thaliana T-DNA insertion mutants lacking expression of the previously identified genes annotated as uridine ribohydrolases (URH1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 55 publications
5
48
0
Order By: Relevance
“…Isolated NSH2 has not yet been characterized biochemically, but extracts of an nsh2 mutant line show strongly reduced xanthosine hydrolase activity (Riegler et al, 2011). However, the nsh2 mutant does not accumulate xanthosine as observed in the nsh1 mutant (Jung et al, 2011;Riegler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated NSH2 has not yet been characterized biochemically, but extracts of an nsh2 mutant line show strongly reduced xanthosine hydrolase activity (Riegler et al, 2011). However, the nsh2 mutant does not accumulate xanthosine as observed in the nsh1 mutant (Jung et al, 2011;Riegler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that mutation of NSH1 (formerly URH1) of A. thaliana leads to accumulation of xanthosine and uridine in this plant because the enzyme is required for the hydrolysis of both compounds in vivo (Jung et al, 2011;Riegler et al, 2011). We crossed plants carrying the published nsh1-1 allele (SALK_083120) with plants possessing the gsda-2 allele to assess the contribution of GSDA to the xanthosine pool in vivo.…”
Section: Xanthosine Is Exclusively Generated From Guanosine In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…URH1 and URH2 are nucleoside ribohydrolases with inosine and xanthosine hydrolytic activity, leading to hypoxanthine and xanthine generation (Riegler et al, 2011). Urease catalyzes the hydrolysis of urea to ammonia and carbon dioxide, which are the final products of purine degradation.…”
Section: Metabolic Profiling Of Loss-of-function Grxs17 Plants Pointsmentioning
confidence: 99%
“…However, it is unclear whether or how uridine is imported into plastids. Pyrimidine and purine-nucleoside cleavage is mainly facilitated by nucleoside hydrolase1 (NSH1), a cytosolic enzyme (Jung et al, 2009, Riegler et al, 2011). The resulting nucleobases can then undergo either salvage by phosphoribosyl-pyrophosphatedependent phosphoribosyl-transferases or catabolism.…”
Section: Introductionmentioning
confidence: 99%